Effectiveness Of Benson Relaxation Therapy And Murottal A Quran On Sleep Quality Of Elderly People Inn Harapan Kita Social Associates Palembang In 2025 - Saputra, Amien; Utama Saputra, Andre; Mardiono, Sasono (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Sleep disorders are common health problems among the elderly that can decrease quality of life and increase the risk of degenerative diseases. Non-pharmacological interventions are considered safe alternatives to sleeping medications, including Benson Relaxation Therapy and Qur’anic Murottal Therapy. This study aimed to examine the effectiveness of both therapies in improving the sleep quality of elderly residents at the Harapan Kita Social Institution in Palembang. A quasi-experimental design with a two-group pretest–posttest design was employed. A total of 30 respondents were selected through purposive sampling and divided into two groups: the Benson Relaxation group and the Qur’anic Murottal group. The Pittsburgh Sleep Quality Index (PSQI) was used as the measurement instrument. Data were analyzed using univariate and bivariate approaches with the Wilcoxon Signed Rank Test and the Mann-Whitney U Test. The results showed a significant improvement in sleep quality in both groups after the interventions (p < 0.05). The study concludes that both Benson Relaxation Therapy and Qur’anic Murottal Therapy are equally effective non-pharmacological interventions to enhance sleep quality among the elderly.